Clinical Features and Histopathologic Examination in Supporting The Diagnosis of Exfoliative Dermatitis Suspected Caused by Captopril in Child : A case report - Awalia Astarina; T Ibnu Alferraly; Deryne Anggia Paramita; Kristo A Nababan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Exfoliative dermatitis (ED) is defined as diffuse erythema and scaling of the skin involving more than 90% of the total body skin surface area. It is a reaction pattern and cutaneous manifestation of a myriad of underlying ailments, including psoriasis and eczema, or a reaction to the consumption of certain drugs. Though some experts believe it does not pose a significant risk of death, erythroderma is a potentially life-threatening condition that requires proper diagnosis, identification of underlying etiology, and management. Several factors have been implicated as triggers for erythroderma and can be grouped into several general categories, including preexisting dermatoses, drugs, and malignancies. Drugs Involved in ED, one of the drugs that cause it is cardiac drugs such as captopril. Captopril, an angiotensin-converting enzyme (ACE) inhibitors containing a sulfhydryl group and has occasionally been implicated in complex immunological diseases, this chemical group has been considered the culprit of allergic reactions to captopril. Histopathologic examination is important to exclude differential diagnosis. Management of ED involves combining symptomatic relief with addressing the underlying etiology and potential systemic complications. In patient hospitalization is required in acute cases.